If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-4(x-3)=15x-7
We simplify the equation to the form, which is simple to understand
9x-4(x-3)=15x-7
Reorder the terms in parentheses
9x+(-4x+12)=15x-7
Remove unnecessary parentheses
+9x-4x+12=+15x-7
We move all terms containing x to the left and all other terms to the right.
+9x-4x-15x=-7-12
We simplify left and right side of the equation.
-10x=-19
We divide both sides of the equation by -10 to get x.
x=1.9
| 12m^3+3m^2+9m=0 | | 4(1)=y+3 | | (2x+6)+(3x+2)=0.5 | | 6(-8r-2)= | | 4(-1)=y+3 | | 74-b=19 | | 65=z+19 | | 3q=27 | | 3-c=14 | | 62=71-s | | 9x=2y+23 | | -5(a)+7=43 | | -3n-6=n-4 | | 62=71-2 | | n^(1/3)-6=0 | | 3x(x-2)-3(x-2)(x+2)=(x+1)(x+2) | | p-8/5=5p-8/4 | | log(8x+8)=2 | | 7-5(a)=43 | | 35/t=5 | | 4(6b+8)=2(11b+30) | | r+14=58 | | 64=90-f | | 129=41+e | | 9u=54 | | a+5=-10a+5 | | 38=t-13 | | 30w+200=20w+450 | | 2^3•4^3•5/5^2•2^4 | | (t+6)(t-6)=-16t | | -18-6k=6(7+9k) | | 113=31+a |